1991
DOI: 10.1007/bf00263189
|View full text |Cite
|
Sign up to set email alerts
|

Optic chiasm glioma associated with inappropriate secretion of antidiuretic hormone, cerebral ischemia, nonobstructive hydrocephalus and chronic ascites following ventriculoperitoneal shunting

Abstract: An optic chiasm glioma may cause loss of vision, endocrine disturbances, hydrocephalus and cerebral ischemia due to its proximity to the pituitary, hypothalamus, III ventricle and internal carotids. A 3-month-old infant with optic chiasm glioma developed hypopituitarism and inappropriate secretion of antidiuretic hormone with plasma hypo-osmolality. The cerebrospinal fluid (CSF) protein concentration was markedly elevated. The impairment of fluid absorption via arachnoid villi and peritoneum by the high protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
2
13
0
3
Order By: Relevance
“…According to this supposition, an elevated CSF protein content may lead to reversed osmosis at the level of the blood-brain barrier with the resultant accumulation of excessive CSF fluid within the peritoneal cavity [13]. However, numerous cases of high CSF protein without resultant ascites have been reported [9].…”
Section: Discussionmentioning
confidence: 99%
“…According to this supposition, an elevated CSF protein content may lead to reversed osmosis at the level of the blood-brain barrier with the resultant accumulation of excessive CSF fluid within the peritoneal cavity [13]. However, numerous cases of high CSF protein without resultant ascites have been reported [9].…”
Section: Discussionmentioning
confidence: 99%
“…The overall 5-year survival rate of patients with chiasmatic and hypothalamic gliomas is reported to vary between 40 and 88% [8, 17]. Patients with an optic pathway tumor and neurofibromatosis type I have a better prognosis than those who do not have neurofibromatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al [8] reported a 3-month-old female infant, who developed staring spells, twitching of the right eyelids, and extensive movements of the right arms, the CT scan revealed a lesion involving both optic nerves, optic chiasm, left optic tract and geniculate body and the histopathological diagnosis was astrocytoma. In a series of 19 cases with chiasmal/hypothalamic gliomas reported by Petronio et al [9], visual impairment, obstructive hydrocephalus and endocrinopathies were common presenting symptoms [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iraci et al [23] reported a series of 5 patients with precocious or pseudoprecocious puberty associated with optic nerve gliomas. Patients with suprasellar tumors have also presented with symptoms of diabetes insipidus [24], syndrome of inappropriate antidiuretic hormone hypersecretion [25], gigantism [26,27], growth hormone deficiency [28], hypothyroidism, adrenal insufficiency, and gonadotropin insufficiency [29]. Ahn et al [29] presented a series of 33 patients who underwent surgery for optic pathway gliomas; 19 had preoperative endocrine abnormalities.…”
Section: Discussionmentioning
confidence: 99%